Zero Prep - Activities for All Levels : Ready-to-Go Activities for In-Person and Remote Language Teaching - Pollard, Laurel, ....-; Hess, Natalie, ....-; Marell, Michal, ....- (Rockville : Pro Lingua Learning, 2023)
First, we identified the BEST teaching strategies and activities for the language classroom. Then we kept only the ones that require ZERO PREPARATION for the teacher. Finally, from that carefully curated collection, we kept only the activities that are most ADAPTABLE for various language levels and for in-person and remote instruction. For the teacher, these activities reduce "PREP" time, the short-term tasks that can eat up our attention, inspiration, and energy. This gives us more time to PLAN: to think about our students' goals and how to help them get there. For our students, these carefully crafted activities help them take charge of their own learning. The result: they learn more and remember waht they've learned. These new Second Editions feature: online adaptations for every activity, dozens of new activities, a companion online guide, Supercharge Your Teaching, full of research-based tips that will transform your life as a teacher.
Keywords: Engels secundair onderwijs